Control of mergers and acquisitions in European Union and Turkish law - Yurttaş, Yalçın (My University, 2015)
Bu çalışmanın amacı; Avrupa Birliği ve Türkiye'de şirket birleşme ve devralmalarının denetlenmesinin gelişimini hukuki ve tarihi bir perspektiften incelemek ve bu iki denetleme rejimi arasındaki etkileşimi, ekonomik, sosyolojik ve teorik arka planı ile ortaya koymaktır. Bu çalışmanın konusu, yalnızca şirket birleşme ve devralmalarının denetlenmesinin usul kuralları değil aynı zamanda tarihi kökenleri ve toplum, ekonomi ve Avrupa Birliği ve Türkiye ilişkileri üzerindeki etkisi ile farklı 'ekollerin' bu mevzuda yapmış olduğu teorik katkılardır. Bu tez, Avrupa Birliği ve Türkiye'deki şirket birleşme ve devralmalarının denetlenmesi rejimlerinin oluşum ve işleyiş süreçlerindeki benzerlik ve farklılıkları ortaya koymayı amaçlamaktadır. Avrupa Birliği, Birleşme, Denetleme, Devralma, Türkiye.

The objective of this study is to scrutinize the development of control of concentrations in European Union and Turkey from a legal and historical point of view and to analyze the interaction between the two concentration control regimes, together with their economic, sociological and theoretical background. The subject of this study is not only the procedural aspects of concentration control, but also its historical roots and impacts upon the society, economy and the relationship between European Union and Turkey, together with the various valuable theoretical contributions made by different 'schools' upon it. This thesis aims at depicting the differences and similarities within the production and formation of the Union and Turkish concentration control regimes. Key words: acquisitions, concentrations, control, EU, mergers, Turkey.
Keywords: Avrupa Birliği ülkeleri; Yasa ve yasama